Cancer in literature: between phenomenology and symbolism - Engelhardt, Dietrich von (Ethical challenges in cancer diagnosis and therapy, 2021)
Cancer has been an important theme in literature, especially since the nineteenth century. Central dimensions of the frequent literary representations and interpretations of cancer are pathophenomenology, aetiology, diagnosis and therapy, image of the physician, subjectivity of the patient, medical institutions, social reactions and symbolism. The relationship between literature and medicine is a complex and reciprocal one marked by ontological differences. The long tradition of 'medical humanities' dating from ancient to present times is essential as human and humane medicine for the benefit and dignity of the suffering, sick and dying.